Inorganic sputtered coating to win gold medals at winter olympics - Lefebvre, P.; Wolfsperger, F.; Herody, J.; Jaggi, J.; Mantoux, A.; Coulmy, N.; Hagenmuller, P.; Blanquet, E. (10th International Congress on Science and Skiing, January 28 - February 1, 2025, Val di Fiemme, Italy, 2025)
INTRODUCTION: In cross-country skiing, reducing the friction coefficient between the skis and snow is essential for sportive performance [1]. Fluorinated waxes, i.e. containing perfluoroalkyl (PFA) are known for their hydrophobic properties and were remarkably efficient in wet snow conditions. However, the International Ski and Snowboard Federation (FIS) has banned fluorinated wax since winter 2023/2024 -for health and environmental reasons [2]. Since then, no alternative with equivalent performance has been found. This project aims to develop hard and hydrophobic coatings based on titanium nitride (TiN), aluminum nitride (AlN) and alumina (Al2O3) materials deposited on ski bases and UHMW polyethylene.